Young athletes with ventricular premature beats: Continuing or not intense training and competition? - Parisi, A.; Tranchita, E.; Minganti, C.; Sperandii, F.; Guerra, E.; Calo, L.; Borrione, P.; Pigozzi, F. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Introduction: Isolated ventricular premature beats (VPBs) are commonly found during pre-participation screening in athletes. Currently the debate about the role of detraining in reducing the number of VPBs is still open.